Ler para Ver - Sabino, Ana (MATLIT: Materialities of Literature, 2016)
Recensão Crítica de Peter MENDELSUND, What we see when we read, Nova Iorque, Vintage Books, 2014, 448 pp. ISBN 978-0-8041-7163-2 DOI: http://dx.doi.org/10.14195/2182-8830_4-1_18